Kekuatan Mengikat Konvensi Ketatanegaraan dalam Penetapan Waktu Pelantikan Presiden: Urgensi Kodifikasi dalam Sistem Hukum Indonesia - Kiki Fatmawati; Rosmini Rosmini; Herdiansyah Hamzah (JUNCTO: Jurnal Ilmiah Hukum, 2026)
This article aims to analyze the role of constitutional conventions in determining the timing of the inauguration of the President and Vice President, as well as to examine the legal and political implications should the inauguration not be conducted in accordance with established conventions. The focus is on the legal vacuum that results in the practice of holding the inauguration on October 20 being based solely on unwritten conventions without formal sanctions. To address this issue, the author draws upon the theory of constitutional conventions according to Dicey and Jennings, as well as legal-political theory. Data were collected through a literature review using primary, secondary, and tertiary legal sources and analyzed qualitatively using a normative legal research method that employs statutory, conceptual, and comparative approaches. This study concludes that the October 20 inauguration convention functions as unwritten law that is morally and politically binding but lacks formal legal force, and that deviations from this convention have the potential to create legal uncertainty, a crisis of legitimacy, and a threat to the stability of Indonesia's presidential system. This study offers a normative model for codifying constitutional conventions into positive law as an effort to strengthen legal certainty and prevent constitutional crises in national leadership succession, filling the gap in existing literature that has not specifically examined the urgency of codifying the timing of presidential inauguration.